Penyusunan Bahan Ajar Mata Pelajaran Finance Accounting Pada SMK Batam Business School - Anita Anita; Twyra Huang (Universitas Internasional Batam, 2021)
Teaching materials play an important role for teachers in learning process with students in schools, one of which is the Batam Business School Vocational High School. The lack of modification of teaching materials and less updated reference sources in Financial Accounting class XI odd semester is a problem that is being faced by Batam Business School Vocational High School in the midst of COVID-19 pandemic in using online learning models. This learning model utilizes available technology and applications so that the world of education can continue. The methods used to solve this problem are the interview method and the documentation method. The output of this activity, there are ten files of powerpoint and three learning videos that can be accessed on Youtube that related to material on credit sales transactions, installment sales, and drafts, accounts receivable, the method of eliminating uncollectible accounts receivable, notes receivable, accounts receivable card, accounts payable short term, accounts payable card, inventory, inventory valuation methods, and cost of goods manufactured. The results achieved from this activity are the Financial Accounting subject teacher at SMK Batam Business School felt helped in the preparation of odd semester teaching materials that would be used in the learning process with XI grade students and in accordance with the basic competencies applied in schools.